1996
DOI: 10.1177/0306624x9604000303
|View full text |Cite
|
Sign up to set email alerts
|

The Childhood Victimization of Sex Offenders: An Underestimated Issue

Abstract: The childhood victimization of sex offenders was investigated. The victimization experiences were recorded from a treatment milieu for sex offenders. Two hundred and eighty-six offenders were involved in the study. Comparisons were done between groups to determine relationships between alienation, dissociation, social desirability, and victimization experiences. Seventy percent of the sample admitted to being sexually abused as a child, 50% admitted to physical abuse. Offenders who were both sexually and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 33 publications
1
31
1
1
Order By: Relevance
“…Generic adult sexual offenders appear to have been sexually victimized in childhood more often than the general population or other types of offenders (see, e.g., Bard et al, 1987;Crassati, McClurg, & Browne, 2002;Graham, 1996) and JSOs report a higher prevalence of such abuse in their developmental histories than various controls (see, e.g., Burton et al, 2002;Seto & Lalumière, 2004;Zakireh et al, 2008). Such abuse of JSOs has been found to covary with the characteristics of their future perpetration, such that youth who have been abused repeat sexually aggressive behaviors that were used by their own victimizers (Burton, 2003b;DiCenso, 1992).…”
Section: Sexual Victimizationmentioning
confidence: 99%
“…Generic adult sexual offenders appear to have been sexually victimized in childhood more often than the general population or other types of offenders (see, e.g., Bard et al, 1987;Crassati, McClurg, & Browne, 2002;Graham, 1996) and JSOs report a higher prevalence of such abuse in their developmental histories than various controls (see, e.g., Burton et al, 2002;Seto & Lalumière, 2004;Zakireh et al, 2008). Such abuse of JSOs has been found to covary with the characteristics of their future perpetration, such that youth who have been abused repeat sexually aggressive behaviors that were used by their own victimizers (Burton, 2003b;DiCenso, 1992).…”
Section: Sexual Victimizationmentioning
confidence: 99%
“…Research indicates that sexual abuse histories are prevalent in sex offenders (Dwahan & Marshall, 1996;Graham, 1996;Jesperson, Lulumiere & Seto, 2009). Considering that being sexually abused at a young age promotes sexual deviancy, it"s suggested that sexual abuse histories are a primary cause to future sexual offending (Lindsay, Steptoe & Haut, 2011).…”
mentioning
confidence: 99%
“…There has been much interest in the victim/offender hypothesis (Burgess et al, 1988;Ryan, 1989;Langevin et al, 1989;Graham, 1996;Romano and De Luca, 1997), an analysis that draws links between sexually abused young people and the possible progression to adult offending. Inherent in this is the notion of a 'cycle of abuse' that reinforces the patterning of abusive behaviours across generations.…”
mentioning
confidence: 99%
“…Some studies report high prevalence of childhood sexual abuse in the sexual offender sample groups, some low. For example, research by Briggs (1995) and Graham (1996) report high levels of child sexual abuse victimisation: Briggs reports 93% and Graham 70%. However, a study by Langevin et al (1989) found that sexual abuse did not appear to have been extensive within the experience of the men in the sample (16%).…”
mentioning
confidence: 99%
See 1 more Smart Citation